2009
DOI: 10.1371/journal.pone.0005930
|View full text |Cite
|
Sign up to set email alerts
|

Protection and Polyfunctional T Cells Induced by Ag85B-TB10.4/IC31® against Mycobacterium tuberculosis Is Highly Dependent on the Antigen Dose

Abstract: BackgroundPreviously we have shown that Ag85B-TB10.4 is a highly efficient vaccine against tuberculosis when delivered in a Th1 inducing adjuvant based on cationic liposomes. Another Th1 inducing adjuvant, which has shown a very promising profile in both preclinical and clinical trials, is IC31®. In this study, we examined the potential of Ag85B-TB10.4 delivered in the adjuvant IC31® for the ability to induce protection against infection with Mycobacterium tuberculosis. In addition, we examined if the antigen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
113
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(125 citation statements)
references
References 24 publications
12
113
0
Order By: Relevance
“…Earlier work showed that the MVA85a TB vaccine candidate was immunogenic in PPD-negative British adults and that the magnitude of the IFN-␥ enzyme-linked immunospot assay response was positively influenced by BCG priming (26). Our results are promising, since studies in mouse models showed that induction of polyfunctional T cells correlated with protection against tuberculosis (1,19) and that assessment in humans of T-cell polyfunctionality might allow more accurate identification of a protective T-cell population (9). Moreover, it is generally accepted that the induction of cellular Th1 immune responses is associated with protection against TB (36).…”
Section: Discussionsupporting
confidence: 58%
“…Earlier work showed that the MVA85a TB vaccine candidate was immunogenic in PPD-negative British adults and that the magnitude of the IFN-␥ enzyme-linked immunospot assay response was positively influenced by BCG priming (26). Our results are promising, since studies in mouse models showed that induction of polyfunctional T cells correlated with protection against tuberculosis (1,19) and that assessment in humans of T-cell polyfunctionality might allow more accurate identification of a protective T-cell population (9). Moreover, it is generally accepted that the induction of cellular Th1 immune responses is associated with protection against TB (36).…”
Section: Discussionsupporting
confidence: 58%
“…It should be noted that although in a recent study we showed that vaccines formulated in IC31 improved their efficacy when Ag dose was reduced to 0.5 mg/animal [18]; in this study we used the CAF01 adjuvant, where the optimal dose for TB10.4 was found to be 5 mg/animal (and changing the dose did not affect the epitope pattern (data not shown).…”
Section: Or Tb104 Expressed By a Live Vectormentioning
confidence: 72%
“…Many different approaches, such as recombinant vaccinia viruses (9), adjuvanted subunit vaccines (10), or genetically modified BCG variants (11), are currently in clinical trials. At the same time, there is a growing interest in characterizing relevant T cell epitopes for incorporation into vaccination strategies, mainly focusing on proteinaceous targets, including the immunodominant early secretory antigenic target, , and its dimerization partner culture filtrate protein, CFP10; different isoforms of Ag 85 (13); and more recently also dormant-phase Ags, such as TB10.4 (14). However, it is increasingly recognized that unconventional epitopes may also play a role in the antimycobacterial immune response.…”
mentioning
confidence: 99%